Mapping eGFR loci to the renal transcriptome and phenome in the VA Million Veteran Program - Jacklyn N. Hellwege (Nature Portfolio, 2019)
Persistently low levels of estimated glomerular filtration rate (eGFR) are a biomarker of chronic kidney disease. Here, the authors reinterpret the genetic architecture of kidney function across ancestries, to identify not only genes, but the tissue and anatomical contexts of renal homeostasis.